Structure and transcription of the tRNAPro1 gene from Escherichia coli. - Kuchino, Y (1985)
A 5 kbp DNA fragment containing the tRNAPro1 gene from Escherichia coli was cloned into Charon 21A phage and sequenced by the M13 DNA sequencing technique. When the cloned DNA fragment was used as a template for in vitro transcription with E. coli RNA polymerase, a tRNAPro1 precursor of 120 nucleotide residues was obtained. The tRNAPro1 gene transcribed as a single transcription unit was followed by two unusual repeating sequences, both of 108 bp. These two repeating sequences were separated by a 60 bp spacer sequence. The 5'-portion of each repeating sequence overlapped 19 bp of the 3'-terminal region of the tRNAPro1 gene just like the repeating sequences in the E. coli tRNATyr1 gene. A rho-independent termination was present in the first repeating unit.